2000
DOI: 10.1037/0278-7393.26.6.1666
|View full text |Cite
|
Sign up to set email alerts
|

Competing strategies in categorization: Expediency and resistance to knowledge restructuring.

Abstract: The authors investigated people's ability to restructure their knowledge when additional information about a categorization task is revealed. In 2 experiments, people first learned to rely on a fairly accurate (but imperfect) predictor. At various points in training, a complex relationship between 2 other predictors was revealed in a schematic diagram that could support perfect performance. In Experiment 1, people adopted the complex strategy when it was revealed at the outset but were unable to restructure th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
56
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(60 citation statements)
references
References 30 publications
4
56
0
Order By: Relevance
“…Turning first to points of agreement, our results confirm the necessity of providing a hint about an alternative strategy, since no restructuring was observed when the reveal manipulation was withheld. This accords well with the findings by Kalish et al (2005) and Lewandowsky et al (2000), who similarly found that even after extended learning people did not spontaneously abandon one strategy in favor of another. Moreover, in Lewandowsky et al's study, when the alternative strategy was revealed after training, participants resisted knowledge restructuring and continued to use the originally learned strategy.…”
Section: Connections To Previous Researchsupporting
confidence: 82%
See 3 more Smart Citations
“…Turning first to points of agreement, our results confirm the necessity of providing a hint about an alternative strategy, since no restructuring was observed when the reveal manipulation was withheld. This accords well with the findings by Kalish et al (2005) and Lewandowsky et al (2000), who similarly found that even after extended learning people did not spontaneously abandon one strategy in favor of another. Moreover, in Lewandowsky et al's study, when the alternative strategy was revealed after training, participants resisted knowledge restructuring and continued to use the originally learned strategy.…”
Section: Connections To Previous Researchsupporting
confidence: 82%
“…For this associative-learning account, all items should continue to be categorized into the appropriate training category if they are sufficiently learned. Although this basic idea is compatible with the results of Lewandowsky et al (2000) and Kalish et al (2005), a simple associative-learning view is constrained to expect identical outcomes for all item types, irrespective of whether or not experimental and preexperimental knowledge are in conflict.…”
supporting
confidence: 58%
See 2 more Smart Citations
“…Because average data obscure differences among participants, a k-means clustering analysis was used to explore individual differences in participants' response profiles (see Erickson, 1999;Lewandowsky, Kalish, & Griffiths, 2000;Webb & Lee, 2004;Yang & Lewandowsky, 2003). Profiles consisted of responses to all stimuli across all five phases of the experiment.…”
Section: Resultsmentioning
confidence: 99%